Studi Kelayakan Bisnis Pengembangan Klinik Gigi Berbasis Digital Melalui Pembuatan Aplikasi Tami Dental Care APP - Pri Agung Danarahmanto; Budi Djatmiko (Jurnal Multidisiplin Madani, 2022)
Health is a primary need for humans, so this sector continues to experience growth. This study aims to conduct a business feasibility study and examine several things at a company that provides dental and oral health services in West Java called Tami Dental Care. Assessing decoupling and SWOT aspects, management aspects, marketing aspects, production aspects, human resource management aspects, and financial aspects. The results of the study indicate that based on all aspects and especially the financial aspect, it shows that the making of the TDC App that will be carried out is feasible to run. Companies need to maintain financial performance and continue to be profitable companies. one of them is by making the TDC App application.